Work Stress in Employees in the Field of Apparatus Performance and Awards at the Regional Civil Service Agency of South Sulawesi Province - Fitriani Lengke; Risma Niswaty; Sitti Arhas; Nurfadila Nurfadila (International Journal of Administration and Education (IJAE), 2025)
This study aims to determine Work Stress in Employees in the Field of Apparatus Performance and Awards at the Regional Civil Service Agency of South Sulawesi Province. The approach and type of research used are qualitative research approaches and types of descriptive research, using data collection techniques that are carried out using observation, interview, and documentation methods. The data analysis techniques carried out are data condensation, data presentation, and conclusion drawn. The results of the study show that work stress in Employees in the Apparatus Performance and Awards Division at the Regional Civil Service Agency of South Sulawesi Province exists because there are tasks that cannot be predicted in number and there are obstacles in their completion, there are also employees who increase working hours, in addition to the lack of adequate facilities such as computers, printers and slow internet connections so that it can hinder the work of employees and there are also employees who Given responsibilities outside their field so that it can cause work stress for employees. In personal factors, one of which includes family problems, employees who must divide between work and family responsibilities which cause concentration disorders and difficult time management because they have to divide work and responsibilities for their families.